2009
DOI: 10.32800/abc.2009.32.0071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Kenkatha and Gaolao (Bos indicus) cattle breeds using microsatellite markers

Abstract: One hundred forty–five individuals from two cattle breeds, Kenkatha and Gaolao, in India were studied using 25 fluorescently–labelled microsatellite markers. Genetic diversities within and between populations were studied. A total of 197 and 239 distinct alleles were identified across 25 microsatellite loci in Kenkatha and Gaolao cattle, respectively. Means of observed and expected heterozygosity were found to be 0.47 ± 0.24 and 0.62 ± 0.21 in Kenkatha, and 0.53 ± 0.17 and 0.68 ± 0.14 in Gaolao cattle, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Allele size of the eight markers (MM8, INRA063, BM1818, ILSTS054, ILSTS005, HEL5, ILSTS006 and ILSTS011) ranged from 125-169bp, 163-215bp, 213-285bp, 110-167bp, 160-192bp, 127-193bp, 260-329bp and 240-270bp, respectively in Siwa and Farafra cattle populations (Table 2). Results agree with the selective standard of the microsatellite loci (the Secondary Guidelines for Development of National Farm Animal Genetic Resources using reference Microsatellite given by FAO, 2004).In Gaolao and Kenkatha cattle, Chaudhari et al (2009) found that allele size ranged from 118-150bp, 170-188bp, 258-280bp, 176-190bp, 279-301bp and260-272bp with MM8, INRA063, BM1818, ILSTS005, ILSTS006 andILSTS011, respectively. Gralak et al (2004) reported that the size ranged from 262-264bp, 282bp with BM1818 and ILSTS006, respectively in European bison bovine.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Allele size of the eight markers (MM8, INRA063, BM1818, ILSTS054, ILSTS005, HEL5, ILSTS006 and ILSTS011) ranged from 125-169bp, 163-215bp, 213-285bp, 110-167bp, 160-192bp, 127-193bp, 260-329bp and 240-270bp, respectively in Siwa and Farafra cattle populations (Table 2). Results agree with the selective standard of the microsatellite loci (the Secondary Guidelines for Development of National Farm Animal Genetic Resources using reference Microsatellite given by FAO, 2004).In Gaolao and Kenkatha cattle, Chaudhari et al (2009) found that allele size ranged from 118-150bp, 170-188bp, 258-280bp, 176-190bp, 279-301bp and260-272bp with MM8, INRA063, BM1818, ILSTS005, ILSTS006 andILSTS011, respectively. Gralak et al (2004) reported that the size ranged from 262-264bp, 282bp with BM1818 and ILSTS006, respectively in European bison bovine.…”
Section: Resultssupporting
confidence: 84%
“…recorded that the number of observed alleles varied between 3 (ILSTS011) to 10 (ILSTS034) with an overall mean number of 5.95±1.9 alleles per locus. Chaudhari et al (2009) observed a total of 239 and 197 distinct alleles with mean values of 9.52 and 7.92 in Gaolao and Kenkatha cattle, respectively. They also, reported that alleles observed per locus ranged between 5 (loci ILSTS006 and ILSTS030) and 15 (locus ILSTS034) and between 4 (locus ILSTS006) and 14 (loci BM1824 and ILSTS006) in Gaolao and Kenkatha cattle, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The other populations had average heterozygosities between 0.650 and 0.737. These results were very similar to those observed in Gobra populations from the groundnut basin, Moorish from the river valley and N'dama from the CRZ of Kolda in Senegal (Ndiaye et al., 2015); taurine breeds or zebu breeds found in Africa (Dayo et al., 2009; Freeman et al., 2004; Foulley & Ollivier, 2006; MacHugh et al., 1997; Ngono Ema et al., 2015); Asian zebu (Chaudhari et al., 2009; Sharma et al., 2009; Shi et al., 2010; Suh et al., 2014; Singh et al., 2015); European cattle breeds (Dayo et al., 2009; Freeman et al., 2004; Foulley & Ollivier, 2006; MacHugh et al., 1997) and Brazilian breeds (da Silva Filho et al., 2014). This indicates a high genetic diversity observed across the loci studied.…”
Section: Resultssupporting
confidence: 80%
“…Asian zebu (Chaudhari et al, 2009;Sharma et al, 2009;Shi et al, 2010;Suh et al, 2014;Singh et al, 2015); European cattle breeds (Dayo et al, 2009;Freeman et al, 2004;Foulley & Ollivier, 2006;MacHugh et al, 1997) and Brazilian breeds (da Silva Filho et al, 2014). This indicates a high genetic diversity observed across the loci studied.…”
Section: Discussionmentioning
confidence: 99%